2009
DOI: 10.1089/jmf.2008.0118
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Intake by Canadian Women Is Variable, Similar Among Different Ages, But Greater Than That Reported for Women in Other Countries

Abstract: Lycopene is an antioxidant associated with a reduced risk of chronic diseases common in women such as osteoporosis and cancer; however, no official recommendation for lycopene consumption exists, and intake data from Canadian women are limited. This study was designed to generate information about average lycopene intake in Canadian women of different ages. A cross-sectional study was conducted at St. Michael's Hospital in Toronto, Ontario, Canada. One hundred one women, between the ages of 25 and 70 years, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Rao and Shen ( 54 ) pointed out that when the daily intake of lycopene in healthy adults reaches 57 mg, the concentration of lycopene in the blood may be sufficient to resist oxidative stress and various chronic diseases. A Canadian epidemiological study showed that the average daily intake of lycopene per woman is 6.14 ± 5.35 mg ( n = 101) ( 55 ); another epidemiological study showed that the average daily dietary intake of lycopene in healthy women was 9.25 ± 6.43 mg ( n = 632), and in breast cancer patients was 7.12 ± 6.73 mg ( n = 122) ( 56 ). Thus, the effective dosage of lycopene to have an anti-metastasis efficacy i.e., 6.96 mg/day obtained by the results of this study is not difficult to achieve from a dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Rao and Shen ( 54 ) pointed out that when the daily intake of lycopene in healthy adults reaches 57 mg, the concentration of lycopene in the blood may be sufficient to resist oxidative stress and various chronic diseases. A Canadian epidemiological study showed that the average daily intake of lycopene per woman is 6.14 ± 5.35 mg ( n = 101) ( 55 ); another epidemiological study showed that the average daily dietary intake of lycopene in healthy women was 9.25 ± 6.43 mg ( n = 632), and in breast cancer patients was 7.12 ± 6.73 mg ( n = 122) ( 56 ). Thus, the effective dosage of lycopene to have an anti-metastasis efficacy i.e., 6.96 mg/day obtained by the results of this study is not difficult to achieve from a dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…The range of lycopene intake was quite wide, from 0 to 12.3 mg per day, with 39% of participants consuming 2 mg or less per day. In North America, approximately 50% of the population consume a relatively low intake of 2 mg or less of lycopene per day (3), however, according to studies by us and others (31,32) the average lycopene intake in Canadian women is approximately 5-6 mg/day. Considering the fact that the majority of clinical trials supply at least 15 mg/day to determine the effects of lycopene (33), an intake of < 2 mg per day is quite low.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Tomato products are frequently consumed in the Western World and a popular tomato product is tomato ketchup [28] , [29] . There are no reports on the effect of tomato ketchup on inflammation.…”
Section: Introductionmentioning
confidence: 99%